INTEGRATED LESSONS IN THE CONTEXT OF PROJECT-BASED LEARNING - Gabrielyan, A. (SUSh Scientific Proceedings, 2023)
The article touches upon integrated lessons as a way for the teacher to show the world to the students, and teach about it, as one unity. Integrated lessons revolve around interdisciplinary connections to exhibit one topic/theme from different perspectives through intersecting points. The importance of integrated lessons is obvious not only in Armenia, but internationally as well. In Armenia it is shown through the implementation of the New Standards. At the same time, we have the instructional approach Project-based learning (PBL) to language learning in this case for foreign languages. Project-Based Learning concentrates on students learning the material through the projects. The projects are supposed to be cooperative, interactive, and based on real-life experiences as much as possible. Both are highly interconnected with a few common points, and we notice a chance to combine them for effective learning. This gives a chance to use them as one for a productive, objective language learning. In this article we also present an example of a lesson plan. The planning is extremely important as it serves as a guideline for the teacher. We believe that in the lesson plan the teacher should show the distinctiveness of each subject, also their interconnections in the lesson plan objectives. The process of lesson planning is quite time-consuming and complicated, still it is the milestone for every lesson.